Identifying The Influences of Compass Limited Edition Shoes Series Characteristics Towards Purchase Intention (Journal of Business and Management, 2022)
Shoe brands use limited-edition shoes as a marketing strategy because it doubles sales. OLE is a limited-edition shoe released once, while RLE is released multiple times. An Indonesian shoe brand, Compass, used this method to boost sales, and it worked. However, it also causes angry to customers who can't buy their products. This study examines how limited-edition Compass shoes affect customer purchase intentions by analyzing profit value and brand trust. PLS-SEM was used to analyze variables in an online survey of 205 buyers of limited-edition compass shoes on Java aged 18 to 40. Results show that in OLE, limited-edition implementation affects customer desire to buy Compass limited edition shoes. Emotional, social, and economic value build brand trust. Consumers' purchase intentions were influenced by emotional and economic value, but not social value. Emotional, social, and economic RLE boost brand trust and consumer buying intentions. Compass must maintain its unique character in each OLE and RLE shoe collection, increase collaboration, provide more information about limited edition shoes, and limit the number of purchases by the same buyer. This increases OLE and RLE consumers' purchase intent by increasing shoe characteristic. This research should help business and marketers understand how to increase purchase intention by releasing limited edition OLE and RLE shoes.Limited Edition Shoes Marketing Series; Perceived Value; Brand Trust; Purchase Intention